(untitled) (BIRDEM Medical Journal, 2014)
Background: Neonatal sepsis is one of the major causes of neonatal morbidity and mortality, particularly in developing countries and it is caused by Gram positive bacteria, Gram negative bacteria and fungi. Thrombocytopenia has been used as an early but nonspecific marker for sepsis. About 75% of culture positive neonates have thrombocytopenia. The severity and duration of thrombocytopenia varies in different types of organism. So, the objectives of this study were to examine platelet counts and platelet indices in neonates with culture proven sepsis and to determine if there was an organism specific platelet response. Methods: This cross- sectional prospective study was carried out in the special care baby unit (SCABU) under department of Paediatrics and Neonatology, BIRDEM General Hospital, Dhaka from November 2008 to September 2009. Results: Total 120 newborn babies with culture positive sepsis were included in this study. Gram positive bacteria was found in 06 (5%), Gram negative bacteria was found in 58(48.3%) and fungi was found in 56 (46.7%) neonates. Thrombocytopenia was found in 95% of culture positive neonates. When compared with neonates with Gram positive sepsis, those with Gram-negative or fungal sepsis had a significantly lower platelet count, platelet nadir and prolonged duration of thrombocytopenia (p=<0.05). Fungal sepsis was also associated with prolonged duration of thrombocytopenia when compared with that of Gram negative sepsis (p=0.03). Conclusion: Neonatal sepsis is frequently associated with thrombocytopenia. However, Gram negative and fungal sepsis is associated with a lower platelet count, platelet nadir and prolonged duration of thrombocytopenia compared with that of Gram positive sepsis. Birdem Med J 2014; 4(2): 79-83